Сравнительный анализ отечественных и зарубежных танков на основе метода сравнения по степени рациональности - Анипко, О. Б.; Борисюк, М. Д.; Бусяк, Ю. М. (НТУ "ХПИ", 2008)
In the paper given is a comparative analysis of different types of home and foreign combat tanks based on the rationality level comparative method, complex parameters as well as on the simulation results, experimental studies involving armored vehicles and heuristic examination results obtained.
Keywords: бронетехника; тактико-технические характеристики; эвристическая экспертиза